2020
DOI: 10.1177/0300985820948823
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin and Hippo Pathway Deregulation in Mammary Tumors of Humans, Dogs, and Cats

Abstract: Mammary cancer is a common neoplasm in women, dogs, and cats that still represents a therapeutic challenge. Wnt/β-catenin and Hippo pathways are involved in tumor progression, cell differentiation, and metastasis. The aim of this study was to evaluate mRNA and protein expression of molecules involved in these pathways in human (HBC), canine (CMT), and feline mammary tumors (FMT). Real-time quantitative polymerase chain reaction (qPCR) for β-catenin, CCND1, YAP, TAZ, CTGF, and ANKRD1, western blotting for YAP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 83 publications
1
10
0
Order By: Relevance
“…In the nucleus, YAP and TAZ bind mainly to TEA domain family member (TEAD) transcription factors to regulate the transcriptional activity of target genes involved in diverse processes [19][20][21][22] Hippo dysregulation has also been linked to various cancers in humans 19,[23][24][25][26][27] and dogs. [28][29][30][31] In breast cancer cells, altered transcriptional activity of Hippo transcriptional target genes has been shown to result in enhanced cell proliferation, cell migration, stem cell self-renewal, epithelial-tomesenchymal transition, metastasis and drug resistance. [32][33][34] Additionally, overexpression of the Hippo effectors YAP and (more importantly) TAZ has been detected in human breast cancer and canine mammary gland tumours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the nucleus, YAP and TAZ bind mainly to TEA domain family member (TEAD) transcription factors to regulate the transcriptional activity of target genes involved in diverse processes [19][20][21][22] Hippo dysregulation has also been linked to various cancers in humans 19,[23][24][25][26][27] and dogs. [28][29][30][31] In breast cancer cells, altered transcriptional activity of Hippo transcriptional target genes has been shown to result in enhanced cell proliferation, cell migration, stem cell self-renewal, epithelial-tomesenchymal transition, metastasis and drug resistance. [32][33][34] Additionally, overexpression of the Hippo effectors YAP and (more importantly) TAZ has been detected in human breast cancer and canine mammary gland tumours.…”
Section: Introductionmentioning
confidence: 99%
“…This pathway consists of an intracellular serine/threonine kinase cascade that regulates the activity of two functionally redundant transcriptional co‐activators, Yes‐associated protein 1 (YAP) and Transcriptional coactivator with PDZ‐binding motif (TAZ). In the nucleus, YAP and TAZ bind mainly to TEA domain family member (TEAD) transcription factors to regulate the transcriptional activity of target genes involved in diverse processes 19–22 Hippo dysregulation has also been linked to various cancers in humans 19,23–27 and dogs 28–31 …”
Section: Introductionmentioning
confidence: 99%
“…Because β-catenin score did not correlate with malignancy, Uneyama et al concluded from their IHC results that dysregulated β-catenin is likely not an important player in feline intestinal tumorigenesis; however, accumulation of β-catenin was evident in 60% of their cases [ 12 ]. Our immunohistochemical examination of feline intestinal carcinomas (22.5% of cases positive for nuclear β-catenin) as well as the high expression of active β-catenin in feline mammary tumors compared to healthy tissue [ 41 ], prompted us to further investigate the role of this key protein in the entity of feline intestinal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although a comprehensive review of mammary carcinoma IHC is not the purpose of our review, IHCs such as PR and estrogen receptor could be useful in a diagnostic setting to establish the origin of the primary tumor if the morphology supports the diagnosis of carcinoma. 66 Secondary CNS round-cell neoplasms typically occur as part of widespread neoplasia and include mainly lymphoma and histiocytic sarcoma. 18,20,36,70,73 Diagnostic confirmation for these neoplasms is similar to that described above for primary CNS round-cell neoplasms.…”
Section: Secondary Cns Neoplasmsmentioning
confidence: 99%